The global business environment : sustainability in the balance - Morrison, Janet (London : Bloomsbury Academic, 2023)
"This text challenges students to think critically about global issues that affect the business environment and provides them with a wealth of pedagogical features that help cement learning. Its coverage includes the economic, political, social, legal, cultural, technological and financial environments. The book is truly global in coverage, with case studies and examples from all over the world, including Afghanistan, China, Sweden and Thailand. It also has a strong focus on ethics, responsibilities and sustainability and what this means for business organizations. Janet Morrison's writing style makes difficult concepts easy to understand and its clarity makes it suitable for students with English as a second language. New to this edition: - The theme of uncertainty in global contexts, examining how best to assess and confront the challenges of uncertainties and risks in the differing dimensions of the business environment - A chapter on the worldwide pandemic and the global business environment - Increased coverage of FDI, industrial policy and global communication - New coverage relating to race relations and decolonising the curriculum - 10 new cases, making a total of 52 cases, with all other cases fully updated - A brand new decision-making feature linked to some of the cases studies"--Provided by publisher.
Includes bibliographical references and index.
Keywords: International economic relations; International business enterprises; International trade; Globalization -- Economic aspects; Competition, International